Fabrication of a magnetic nanocomposite based on natural hydrogel: Pectin, tragacanth gum, silk fibroin, and integrated graphitic carbon nitride for hyperthermia and biological features - Leila Choopani; Hooman Aghamirza Moghim Aliabadi; Fatemeh Ganjali; Amir Kashtiaray; Reza Eivazzadeh-Keihan; Ali Maleki; Milad Salimibani; Amir Hossein Karimi; Nabi Salehpour; Mohammad Mahdavi (Carbohydrate Polymer Technologies and Applications, 2024)
The current study aimed to design and synthesize a new magnetic nanobiocomposite and assess its potential for biological applications and hyperthermia. For this purpose, in the first step, the Pectin (PC) and Tragacanth gum (TG) polymer was synthesized using CaCl2 as a cross-linking agent (PC-TG hydrogel). In the second step, natural Silk fibroin (SF) protein and graphitic carbon nitride (CN) were added to the hydrogel to upgrade the nanobiocomposite's strength and due to CN's pharmacology applications, respectively. Finally, for an enhanced hyperthermia application, PC-TG hydrogel/SF/CN was in situ magnetized with Fe3O4 magnetic nanoparticles (MNPs), and PC-TG hydrogel/SF/CN/Fe3O4 nanobiocomposite was synthesized. By using a vibrating-sample magnetometer (VSM), Fourier-transformed infrared (FTIR), thermogravimetric analysis (TGA), energy dispersive X-ray (EDX), X-ray diffraction (XRD), and field-emission scanning electron microscope (FESEM), the structural features and properties of the PC-TG hydrogel/SF/CN/Fe3O4 nanobiocomposite were determined. This magnetic nanobiocomposite's saturation magnetization value was 14.84 emu g-1. The hemolytic assay of this new nanobiocomposite demonstrated that the hemolysis percentage was 1.07 %, around 99.0 % of cells were able to survive, and the MTT assay was used to assess the anticancer activity against breast cancer cell lines (BT549). Additionally, 62.51 (W g-1) in 200.0 kHz was found to be the greatest specific absorption rate (SAR). These findings suggest that the recently created magnetic nanobiocomposite might function admirably in hyperthermia treatment when exposed to an alternating magnetic field.